Alterations of adipokines, pancreatic hormones and incretins in acute and convalescent COVID-19 children - Anuradha Rajamanickam; Aishwarya Venkataraman; Nathella Pavan Kumar; R. Sasidaran; Arul Nancy Pandiarajan; Nandhini Selvaraj; Ruchi Mittal; K. Gowshika; Sulochana Putlibai; S. Lakshan Raj; Padmasani Venkat Ramanan; Subash Babu (BMC, 2023)
Abstract Background The Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), accountable for Coronavirus disease 2019 (COVID-19), may cause hyperglycemia and additional systemic complexity in metabolic parameters. It is unsure even if the virus itself causes type 1 or type 2 diabetes mellitus (T1DM or T2DM). Furthermore, it is still unclear whether even recuperating COVID-19 individuals have an increased chance to develop new-onset diabetes. Methods We wanted to determine the impact of COVID-19 on the levels of adipokines, pancreatic hormones, incretins and cytokines in acute COVID-19, convalescent COVID-19 and control children through an observational study. We performed a multiplex immune assay analysis and compared the plasma levels of adipocytokines, pancreatic hormones, incretins and cytokines of children presenting with acute COVID-19 infection and convalescent COVID-19. Results Acute COVID-19 children had significantly elevated levels of adipsin, leptin, insulin, C-peptide, glucagon and ghrelin in comparison to convalescent COVID-19 and controls. Similarly, convalescent COVID-19 children had elevated levels of adipsin, leptin, insulin, C-peptide, glucagon, ghrelin and Glucagon-like peptide-1 (GLP-1) in comparison to control children. On the other hand, acute COVID-19 children had significantly decreased levels of adiponectin and Gastric Inhibitory Peptide (GIP) in comparison to convalescent COVID-19 and controls. Similarly, convalescent COVID-19 children had decreased levels of adiponectin and GIP in comparison to control children. Acute COVID-19 children had significantly elevated levels of cytokines, (Interferon (IFN)) IFNγ, Interleukins (IL)-2, TNFα, IL-1α, IL-1β, IFNα, IFNβ, IL-6, IL-12, IL-17A and Granulocyte-Colony Stimulating Factors (G-CSF) in comparison to convalescent COVID-19 and controls. Convalescent COVID-19 children had elevated levels of IFNγ, IL-2, TNFα, IL-1α, IL-1β, IFNα, IFNβ, IL-6, IL-12, IL-17A and G-CSF in comparison to control children. Additionally, Principal component Analysis (PCA) analysis distinguishes acute COVID-19 from convalescent COVID-19 and controls. The adipokines exhibited a significant correlation with the levels of pro-inflammatory cytokines. Conclusion Children with acute COVID-19 show significant glycometabolic impairment and exaggerated cytokine responses, which is different from convalescent COVID-19 infection and controls.